Vale Doug Campbell (1939–2023): A Tribute to a Quiet Achiever and his Contributions to Australian Telecommunications - Holmes, Jim (Journal of Telecommunications and the Digital Economy, 2024)
Doug Campbell commenced his life and career in Canada. He joined the Australian telecommunications sector in mid-career and made extended contributions in many different senior management positions in Telecom Australia and Telstra, particularly in modernising the Telstra network, in establishing and managing Telstra Country Wide, and, then, in the early phase of the national broadband network, in NBN Co. Doug died on 2 December 2023, and is sadly missed by his family, friends and former colleagues. This tribute, to which many have contributed, seeks to set Doug’s life and career in the context of the times. He was at the table, often as the key decision-maker, during many of the significant changes in the telecommunications industry during the last decade of the 20th century and the beginning of the 21st.